Antibacterial activity, cytocompatibility, and thermomechanical stability of Ti40Zr10Cu36Pd14 bulk metallic glass. (December 2022) - Rezvan, Amir; Sharifikolouei, Elham; Lassnig, Alice; Soprunyuk, Viktor; Gammer, Christoph; Spieckermann, Florian; Schranz, Wilfried; Najmi, Ziba; Cochis, Andrea; Scalia, Alessandro Calogero; Rimondini, Lia; Manfredi, Marcello; et al.
Abstract: This paper envisions Ti40 Zr10 Cu36 Pd14 bulk metallic glass as an oral implant material and evaluates its antibacterial performance in the inhabitation of oral biofilm formation in comparison with the gold standard Ti–6Al–4V implant material. Metallic glasses are superior in terms of biocorrosion and have a reduced stress shielding effect compared with their crystalline counterparts. Dynamic mechanical and thermal expansion analyses on Ti40 Zr10 Cu36 Pd14 show that these materials can be thermomechanically shaped into implants. Static water contact angle measurement on samples' surface shows an increased surface wettability on the Ti–6Al–4V surface after 48 ​h incubation in the water while the contact angle remains constant for Ti40 Zr10 Cu36 Pd14 . Further, high-resolution transmission and scanning transmission electron microscopy analysis have revealed that Ti40 Zr10 Cu36 Pd14 interior is fully amorphous, while a 15 ​nm surface oxide is formed on its surface and assigned as copper oxide. Unlike titanium oxide formed on Ti–6Al–4V, copper oxide is hydrophobic, and its formation reduces surface wettability. Further surface analysis by X-ray photoelectron spectroscopy confirmed the presence of copper oxide on the surface. Metallic glasses cytocompatibility was first demonstrated towards human gingival fibroblasts, and then the antibacterial properties were verified towards the oral pathogen Aggregatibacter actinomycetemcomitans responsible for oral biofilm formation. After 24 ​h of direct infection, metallic glasses reported a >70% reduction of bacteria viability and the number of viable colonies was reduced by ∼8 times, as shown by the colony-forming unit count. Field emission scanning electron microscopy and fluorescent images confirmed the lower surface colonization of metallic glasses in comparison with controls. Finally, oral biofilm obtained from healthy volunteers was cultivated onto specimens' surface, and proteomics was applied to study the surface property impact on species composition within the oral plaque. Graphical abstract: Image 1